EFFECTIVENESS OF REFRAMING STRATEGY IN GROUP COUNSELING TO HELP REDUCE STUDENTS FEAR TOWARD SCHOOL CONSELOR - Suciati, Aprilia Dewi; Dharmayana, I Wayan; Sholihah, Afifatus (TRIADIK, 2017)
Abstract: This study was aimed to describe the students' fear perceptions toward the guidance and counseling teachers and to describe the effectiveness of reframing strategy in counseling group to help the reduction of students' fear toward the school counselor of SMA Negeri 1 Central Bengkulu. This study used quasi experimental research method with one group pre-test post-test design. The subject of this study was five students who were selected by purposive proportional sampling which have the highest score at the students' fear toward counselor' questionnaire. The analysis result showed that the students' fear toward the school counselor has deacreased after they got a counseling group by using reframing strategy, it could be seen on the result of processing data with the difference test score was z = -2.041, then p<0.05, sowas rejected. It means that the reframing strategy in counseling group was effective to decrease the students' fear toward the school counselor.Keywords: Reframing strategy, Students' fear toward the guidance and counseling teacher.